Time-dependent Behaviour of Cracked Steel Fibre Reinforced Concrete: from Single Fibre Level to Macroscopic Level - Nieuwoudt, Pieter Daniel (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2015.